Reproduction of the Androgenetic Population of the Asian Corbicula Clam (Bivalvia: Cyrenidae) in the Northern Dvina River Basin, Russia - Yulia V. Bespalaya; Olga V. Aksenova; Alexander V. Kropotin; Alexander R. Shevchenko; Oksana V. Travina (Diversity, 2021)
The Corbicula clam is one of the most successful invaders of aquatic ecosystems and has invaded all continents except Antarctica. The natural dispersion of Corbicula seems to be limited by low winter temperatures that fall below the lower lethal temperatures (0 to +2 °C). However, Corbicula can be found in colder regions, taking refuge in waters heated by thermal power plants. The purpose of this investigation was to study the gonadal histology, reproductive cycle, and the seasonal changes of shell size structure of the Corbicula clam populations in the warm water discharge of the Arkhangelsk thermal power plant (Northwest Russia). Samples were collected monthly from January 2017 to December 2018 and processed using traditional histological and morphological techniques. The number of reproductive periods varied from year to year. It was established that the Corbicula clam has a continuous reproduction period which may be adaptive in unstable environmental conditions. This reproductive strategy is probably aimed at increasing the reproductive success of the population. Our data expand the understanding of reproductive features of the Corbicula clam in harsh environmental conditions. These results could be applied to control, monitoring, and management measures.